Assessing vulnerability to climate change in the Ganges Basin using a combined macro- and micro-level approach. (7th August 2016) - Mohan, Divya; Sinha, Shirish
Abstract : The Ganges Basin, which is critical for the economy and livelihoods of India, is facing a number of pressures due to the impacts of climate change and other non-climatic stressors. These stressors pose a serious threat to the communities and ecosystems in the basin and have aggravated their existing vulnerabilities. There is a need to design and implement appropriate adaptation strategies targeting the most vulnerable communities and ecosystems. However, vulnerability is a dynamic concept and faces spatial and temporal variations. Thus, there is a requirement of assessments of the kind of vulnerabilities and its spatial variations that exist in the Ganges Basin. This paper presents a macro-level or district-level vulnerability assessment carried out for the states of Uttar Pradesh and Uttarakhand within the Ganges Basin followed by a micro-level assessment to understand local factors driving vulnerability. It looks into the spatial vulnerability trends across the two states and also tries to identify the reasons for such trends. The objective of this analysis was to identify the vulnerable groups which can be targeted for implementing adaptation strategies.